The Role of Field Excursions in Linking Theoretical Knowledge with Real-World Geographical Phenomena - Nonkula, Zenande (Journal of Ecohumanism, 2025)
This qualitative case study explored the role of field excursions in connecting theoretical geography knowledge with real-world phenomena, as perceived by B.Ed Humanities student teachers at a South African university. Grounded in David Kolb’s Experiential Learning Theory (ELT) and Lee Shulman’s Pedagogical Content Knowledge (PCK), the study sought to understand how these excursions contribute to effective teacher preparation. Data was collected via a Google Form questionnaire from 20 purposively sampled third-year students (P1-P20) who had recently completed a field excursion. Thematic analysis revealed four key findings: field excursions act as a vital bridge between theory and practice, provide a crucial opportunity for visualisation and concrete experience, foster holistic and contextual understanding, and build participants’ confidence. The findings confirm that field excursions serve as a foundational Concrete Experience (ELT) that is essential for developing the specialized knowledge required for teaching (PCK). The study concludes that field excursions are an indispensable pedagogical tool for preparing competent and confident geography educators within the unique South African context, offering rich, lived experiences that cannot be replicated in a classroom.